2006
DOI: 10.1016/s0022-5347(05)00993-6
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Organ Support and Prevalence by Pelvic Organ Prolapse-Quantification (POP-Q) in Korean Women

Abstract: Vaginal size in Korean women differs from that in Western women. The prevalence of any degree of prolapse was approximately 31.7%. Korean women were at relatively higher risk for anterior and posterior vaginal prolapse than for uterine prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
2
13
1
Order By: Relevance
“…In the current study, as in others, 3,14,22,23 increasing age was found to be an independent risk factor for prolapse. This may be caused by progressive deterioration of the connective tissue-to-muscle ratio, denaturation of collagen biochemistry, and gradual denervation of pelvic floor muscles with advancing age.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, as in others, 3,14,22,23 increasing age was found to be an independent risk factor for prolapse. This may be caused by progressive deterioration of the connective tissue-to-muscle ratio, denaturation of collagen biochemistry, and gradual denervation of pelvic floor muscles with advancing age.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence rate (54%) in our study is similar to those in the last two studies, likely because the demographic characteristics and the socioeconomic status of those women are more similar to those of our study cohort. Additionally, the relative frequency of the different stages in our cohort mirrored those observed in other studies, where the majority of women with prolapse had stage 1 or stage 2 disease (12,14). However, ours was a facility-based study of women who presented themselves at the seven BHUs, thus, limiting generalization to the whole population of Afghan refugees in the Haripur area.…”
Section: Discussionsupporting
confidence: 87%
“…Over half of the study women had some degree of genital prolapse. There have been few studies on the prevalence of prolapse among women in lowresource settings, with rates ranging from 31.7% in Korea (12) to 46% in rural Western Gambia (13) and 53% in Iran (14). The prevalence rate (54%) in our study is similar to those in the last two studies, likely because the demographic characteristics and the socioeconomic status of those women are more similar to those of our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we did not observe significant associations of age(1,2,6-8,10), race(2,6), hysterectomy(6), estrogen use(2), and body mass index (2,7,8), with pelvic organ descent. It is possible that factors not measured in the study or factors beyond those currently identified (e.g.…”
Section: Commentcontrasting
confidence: 74%